O056 The effect of acetazolamide and oxygen (ACZ+O2) combination therapy on loop gain and OSA severity. (9th November 2022) - Landry, S; Collet, J; Thomson, L; Beatty, C; Mann, D; Wong, A; Turton, A; Sands, S; Joosten, S; Hamilton, G; Edwards, B
Abstract: Introduction: One third of patients with OSA have high loop gain. Acetazolamide (ACZ) and supplemental oxygen (O2) individually reduce loop gain (via different mechanisms) and the apnoea-hypopnoea-index (AHI). The current study aimed to explore the efficacy of combining both ACZ and O2 to maximally lower loop gain. Method: Randomised single-blind cross-over trial. Participants took ACZ (500mg orally) or placebo for 7 days. Within each arm, participants completed two polysomnograms (PSGs) during which they slept with supplemental oxygen (3L/min) or sham-air. Sleep and respiratory events were scored by a (blinded) technologist. In addition to standard scoring, respiratory events were scored without SpO2 or arousal information to calculate a 'flow-based AHI' (fAHI). PSG data were then imported into Matlab for loop gain analysis. Results: Nine participants (5 males, Age=52.4±9.1, BMI=32.0±4.9, AHI=39.9±22.0) have so far completed the trial. Loop gain was significantly reduced by ACZ (-22%, -0.15 CI95:-0.03 to -0.26, p=0.011), O2 (-25%, -0.19 CI95:-0.08 to -0.29, p=0.001) and combination ACZ+O2 (-33%, -0.23 CI95:-0.12 to -0.34, p<0.001) relative to placebo-sham-air condition. Similarly, fAHI was significantly reduced by ACZ (-34%, -15.7/hr CI95:-8.6 to -22.7, p<0.001), O2 (-21%, -10.2/hr CI95:-3.1 to -17.3, p<0.001) and ACZ+O2 (-45.2%, -21.3/hr CI95:-14.6 to -28.4, p<0.001). While fAHI was significantly lower on ACZ+O2 compared with O2 (p=0.003), the difference between ACZ+O2 and ACZ was not significant (-5.6/hr, p=0.12). ACZ+O2 induced a >50% reduction in fAHI in 4/9 participants. Discussion: Our preliminary data demonstrate that ACZ+O2 may be an efficacious combination therapy for some OSA patients.